Participating in Negotiation of a New Ocean Treaty Under the Law of the Sea Convention – Experiences of and Lessons From a Group of Small-Island Developing States - Hassanali, Kahlil (Frontiers in Marine Science, 2022)
Negotiations are currently underway into establishing a new international agreement under the United Nations Convention on the Law of the Sea (UNCLOS) on the conservation and sustainable use of marine biological diversity of areas beyond national jurisdiction. This paper discusses some of the experiences and challenges faced by the Caribbean Community (CARICOM), a regional group of small island developing States, in the negotiation of this agreement. The group has been engaged as a bloc since the preparatory stage of the process. The process has now advanced well into an inter-governmental conference, which had an original mandate for four sessions, but will be extended for at least one more session in August 2022. CARICOM has managed to innovate, adapt and access and pool resources in order to be relevant and impactful participants throughout the ongoing negotiations and in face of the Covid-19 pandemic. Some suggestions are offered with a view to ensuring continued meaningful involvement of the group in the remainder of the negotiations, as well as in future ocean related multilateral processes.